Sprinkler Method of Irrigation for Wheat Crop in Light Soils Of Rajasthan - Ram, R S; Jain, T C; Jain, K C (Annals of Arid Zone, 2016)
Sprinkler method of irrigation was studied for optimum uniformity coefficient in wheat Crop on Sandy Soil of Jobner. The Sprinkler system when operated at 12.2m X 12.2m spacing with a nozzle size 6.25mm at a pressure of 1.98 kg/cm2 resulted in 84.6 percent uniformity coefficient with wind velocity less than 8.7 km/hr. It produced 27.2 q/ha of wheat and gave 3.86 kg/ha/mm productive efficiency of water. Average application and distribution efficiencies were 60.4% and 90.3% respectively. Total quantity of water pumped at source was 990 mm in the season.